Analisis Korelasi dan Analisis Lintas Genetik Sifat Kuantitatif Terhadap Bobot Buah per Tandan Kelapa Sawit - Simanjuntak, Yuni S; Laisina, Janne K J; Jambormias, Edizon; Natawijaya, Azis (JURNAL BUDIDAYA PERTANIAN, 2025)
This research was aimed to analyze the direct and indirect effect of quantitative properties on the weight of the fruit per bunch, obtain properties that can be used as selective characteristics, and implement them from October 2023 to March 2024 in District Farms 10 PT. BGA, West Kalimantan Province. The method used in this study is an inter-clone design and a single-factor clone that uses nine Tenera clones. Data analysis using multivariate analysis of variance correlation tests and path analysis. The results of the study showed a significant correlation coefficient between phenotype and genotype properties. The path analysis results showed that there is a different direct and indirect correlation between the influence of the quantitative properties on the weight of fruit per bunch. The properties of the number of fruits per bunch and the mass of the bunch can be used as indicators of selection based on the phenotype, whereas the characteristics of the weight and height of the plant can be interpreted as selective indicators based on genotypes.